The characterization of trachelectomy for benign and precancerous indications in Taiwan: A population-based study, 1998-2013 - Jerry Cheng-Yen Lai; Hung-Hui Chen; Chia-Sui Weng; Yiing-Jenq Chou; Nicole Huang; Shih-Yi Wen; Shih-Chun Wang; Kung-Liahng Wang (Elsevier, 2017)
Objective: The study aimed to update the utilization trend and characterize the trachelectomy for benign and precancerous indications in Taiwanese women by comparing associated women, surgeon, and hospital-related characteristics. Materials and methods: We conducted a population-based trend study using inpatient admission claims data from Taiwan's National Health Insurance program from 1998 to 2013. After excluding those who had prior subtotal hysterectomy, women who underwent trachelectomy for benign and precancerous indications were compared by age at surgery (younger than 40 years, n = 130; 40 and 59 years, n = 429; and 60 years or older, n = 439). Trend analysis by age groups and indication was performed for the utilization of trachelectomy. A separate descriptive analysis was also performed to evaluate the surgeon's total trachelectomy case volume during the study period. Results: A total of 998 women who underwent trachelectomy for benign and precancerous indications were included in the study cohort. The overall utilization increased considerably by 100% over the study period. The most common indications for trachelectomy were genital prolapse (75.2%) and precancerous cervical lesion (21.0%). The majority of trachelectomies were performed with concomitant colporrhaphy for genital prolapse among older women without comorbid illness or any prior catastrophic illness. Most women (62.9%) were operated by a relatively small number of surgeons with high case volume (12.6%) during the study period. Compared to women older than 40 years, younger women had less comorbidities, more likely to be treated at private medical institution by surgeons of high case volume, and were less likely to undergo concomitant anterior and posterior colporrhaphy. Conclusions: The overall utilization of trachelectomy for benign and precancerous indications has increased over the past 16-years from 1998 to 2013, particularly among older Taiwanese women without comorbid illness or any prior catastrophic illness.